Partial characterization of a Candida albicans fimbrial adhesin. - Yu, L (1994)
Candida albicans is the primary etiologic agent of candidiasis, a disease that can vary from superficial mucosal lesions to life-threatening systemic or disseminated diseases. Strains of C. albicans have been reported to possess long, thin filamentous protein cell surface appendages termed fimbriae (R.B. Gardiner, M. Canton, and A. W. Day, Bot. Gaz. 143:534-541, 1982). These fimbriae were isolated, purified, and partially characterized. The major structural subunit of the fimbriae is a glycoprotein which consists of 80 to 85% carbohydrate (consisting primarily of D-mannose) and 10 to 15% protein. The molecular weight of the glycosylated fimbrial subunit is approximately 66,000, while unglycosylated protein has an approximate molecular weight of 8,644. The fimbriae function as adhesins mediating C. albicans binding to human buccal epithelial cells. Amino acid analysis of the purified fimbrial subunit indicates that the fimbrial subunit is composed of 50% hydrophobic amino acid residues. The N terminus of the fimbrial subunit is blocked to N-terminal sequencing.